2017
DOI: 10.1016/j.healun.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of humoral immunity profiles to identify heart recipients at risk for development of severe infections: A multicenter prospective study

Abstract: Early immunologic monitoring of humoral immunity profiles proved useful for the identification of heart recipients who are at risk of severe infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 24 publications
(34 reference statements)
1
33
2
Order By: Relevance
“…Th T e strength h of the study is to provide d evide d nce that the identification of the CD CD16 profi f le Previous studies have identified CMV infection as a risk factor associated with the development of allograft vascular lesions 33,34 . In the present cohort, the FCGR3A-VV genotype was identified as a risk factor associated with viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…Th T e strength h of the study is to provide d evide d nce that the identification of the CD CD16 profi f le Previous studies have identified CMV infection as a risk factor associated with the development of allograft vascular lesions 33,34 . In the present cohort, the FCGR3A-VV genotype was identified as a risk factor associated with viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis of liver recipients included in a clinical trial evaluating the effect of CMV-specific hyperimmune globulin prophylaxis on the prevention of disease and its complications suggested that HGG was associated to both the occurrence and the relapse of CMV disease after transplantation. 48 The results from a meta-analysis suggested that severe IgG HGG significantly increases the risk of CMV infection and is associated with higher 1-year all-cause mortality. 47 A recent cohort study of heart transplant recipients demonstrated that the presence of IgG HGG at 7 days after transplantation is a risk factor for CMV disease.…”
Section: Do Neutralizing Antibody Titers Provide Information Regardmentioning
confidence: 99%
“…47 A recent cohort study of heart transplant recipients demonstrated that the presence of IgG HGG at 7 days after transplantation is a risk factor for CMV disease. 48 In addition, in a clinical trial the administration of two monoclonal antibodies in R − kidney recipients at the time of transplant and 1, 4, and 8 post-transplant weeks reduced the incidence of CMV infection, increased the time interval to CMV viremia and was associated with less CMV disease. 49 More recently, early monitoring of specific humoral immunity parameters was proven to be useful for the identification of lung recipients who are at risk of serious infections.…”
Section: Do Neutralizing Antibody Titers Provide Information Regardmentioning
confidence: 99%
See 2 more Smart Citations